2012
DOI: 10.1007/s11572-012-9144-2
|View full text |Cite
|
Sign up to set email alerts
|

Duff on the Legitimacy of Punishment of Socially Deprived Offenders

Abstract: Duff offered an argument for the conclusion that just or legitimate punishment of socially deprived offenders in our unjust society is impossible. One of the claims in his argument is that our courts have the standing to blame an offender only if our polity has the right to do so since our courts are acting as the representatives of, or to use the exact phrases by Duff, ''in the name of'', or ''on behalf of'', the whole polity. In this paper I will challenge that claim. I will argue that the courts can be seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…In between these positions, Peter Chau () has suggested that an unjust state's authority to punish could be partially retained. He draws a distinction between a political community's right to hold offenders to account and the right of its courts to do so.…”
Section: Moral Standing Hypocrisy Complicitymentioning
confidence: 99%
“…In between these positions, Peter Chau () has suggested that an unjust state's authority to punish could be partially retained. He draws a distinction between a political community's right to hold offenders to account and the right of its courts to do so.…”
Section: Moral Standing Hypocrisy Complicitymentioning
confidence: 99%
“…Su obra ha sido extensamente discutida en este aspecto: Cfr Matravers (2006)Holroyd (2010);Chau (2012); Mañalich (2016).…”
unclassified